THERAPEUTIC POSSIBILITIES OF VIRTUAL REALITY TECHNOLOGIES AND MUSIC THERAPY - Romanova, Sanobar Yerejepovna; Muradova, Khurshida Shavkatovna (SCIENCE and SOCIETY, 2026)
This article examines the theoretical aspects of integrating virtual reality technologies and music therapy and analyzes their impact on psychological well-being, emotional stability, and rehabilitation processes. The study demonstrates that music-based interventions in immersive virtual environments can effectively reduce stress and enhance therapeutic outcomes. The combined effects of virtual reality and music therapy are discussed.